Epidemiological and clinical profile of patients with Chagas disease in the Central-North area of Paraná, Southern Brazil - Aretuza Zaupa Gasparim; Carlos Edmundo Rodrigues Fontes; Diogo Francisco Rossoni; Max Jean de Ornelas Toledo (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION Profiles of patients with Chagas disease in Paraná were studied. METHODS A descriptive, questionnaire-based study was performed. RESULTS Of 270 participants, 64% were female, 60% were aged ≥65 years, 91% were infected via vector transmission, and 44% were infected in Paraná. Indeterminate (30%), cardiac (36%), cardiodigestive (20%) and digestive (14%) forms were found. CONCLUSIONS: Patients who were older than 65 years of age, retired, female, living in the urban area of Maringá, and infected by vector transmission in childhood in Paraná presented cardiac and digestive signs and did not receive etiological treatment when first diagnosed.